Interaction with 2, 4-dinitrophenol correlates with polyreactivity, self-binding, and stability of clinical-stage therapeutic antibodies. (December 2021) - Dietlin-Auril, Valentin; Lecerf, Maxime; Depinay, Stephanie; Noé, Rémi; Dimitrov, Jordan D.
Highlights: Human immunoglobulin repertoires contain antibodies that bind to dinitrophenol. Among 112 clinical-stage therapeutic IgG1 antibodies about 20 % bind dinitrophenol considerably. Interaction of antibodies with dinitrophenol correlated with important developability parameters. Abstract: Therapeutic antibodies should cover particular physicochemical and functional requirements for successful entry into clinical practice. Numerous experimental and computational approaches have been developed for early identification of different unfavourable features of antibodies. Immune repertoires of healthy humans contain a fraction of antibodies that recognize nitroarenes. These antibodies have been demonstrated to manifest antigen-binding polyreactivity. Here we observed that >20 % of 112 clinical stage therapeutic antibodies show pronounced binding to 2, 4-dinitrophenol conjugated to albumin. This interaction predicts a number of unfavourable functional and physicochemical features of antibodies such as polyreactivity, tendency for self-association, stability and expression yields. Based on these findings we proposed a simple approach that may add to the armamentarium of assays for early identification of developability liabilities of antibodies intended for therapeutic use.